Numerical prediction of the liberation spectrum of a two-phase texture - G. D. Schena; M Zanin (The Institute of Materials, Minerals and Mining, 1905)
A numerical approach is presented for predicting the liberation of phases during comminution, with direct calculation of a liberation spectrum giving the fraction of the particulate system in each narrow size-composition class. The numerical model uses a Poisson flat process for stochastic generation of the non-convex three-dimensional Poisson polyhedral textures and the system of fractures that give rise to convex fragments. With this numerical approach, there is no need to assume random uniform isotopic fracture (lack of selective liberation); only computational geometry primitives are exploited for the derivation. The agreement with relationships obtained previously under the random uniform isotopic fracture hypothesis demonstrates that the approach is capable of deriving full liberation spectra directly. Both volumetric and superficial composition can be calculated